2011
DOI: 10.1186/1748-5908-6-113
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and implementation of evidence-based practices in public youth-serving systems: a mixed-methods study

Abstract: BackgroundThe present study examines the structure and operation of social networks of information and advice and their role in making decisions as to whether to adopt new evidence-based practices (EBPs) among agency directors and other program professionals in 12 California counties participating in a large randomized controlled trial.MethodsInterviews were conducted with 38 directors, assistant directors, and program managers of county probation, mental health, and child welfare departments. Grounded-theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 26 publications
7
82
0
Order By: Relevance
“…At a basic level, the administrative role is critical for authorizing the time and resources needed to invest in research, gathering and deploying resources to support evidence retrieval, and identifying agency research needs for programs and initiatives (Birkin, Lee, & Weiner, 2012;McBeath & Austin, in press (Moynihan, Wright, & Pandey, 2012) found that transformational leaders promote evidence use indirectly by facilitating goal clarity (around performance targets and pathways) and by supporting a performance-focused organizational culture. This basic finding is supported by other studies referenced in the systematic review conducted by Kroll (2014) as well as research on practitioner evidence use in the human service sector (Palinkas et al, 2011). Research has identified other mechanisms through which agency leaders involve themselves in evidence-informed practice due to the likelihood that they (a) serve as agency representatives for research-based initiatives involving external researchers; (b) are formally responsible for searching for promising practices and identifying evidence-based strategies for responding to current agency dilemmas; (c) oversee data collection and reporting with respect to performance measurement; and (d) organize within-agency communities of learning around professional development and research evidence due to their knowledge of the needs of organizational divisions and key staff (Aarons et al, 2011;Austin et al, 2012;Maynard, 2010).…”
Section: Organizational Factors Promoting Access To Evidencesupporting
confidence: 72%
See 2 more Smart Citations
“…At a basic level, the administrative role is critical for authorizing the time and resources needed to invest in research, gathering and deploying resources to support evidence retrieval, and identifying agency research needs for programs and initiatives (Birkin, Lee, & Weiner, 2012;McBeath & Austin, in press (Moynihan, Wright, & Pandey, 2012) found that transformational leaders promote evidence use indirectly by facilitating goal clarity (around performance targets and pathways) and by supporting a performance-focused organizational culture. This basic finding is supported by other studies referenced in the systematic review conducted by Kroll (2014) as well as research on practitioner evidence use in the human service sector (Palinkas et al, 2011). Research has identified other mechanisms through which agency leaders involve themselves in evidence-informed practice due to the likelihood that they (a) serve as agency representatives for research-based initiatives involving external researchers; (b) are formally responsible for searching for promising practices and identifying evidence-based strategies for responding to current agency dilemmas; (c) oversee data collection and reporting with respect to performance measurement; and (d) organize within-agency communities of learning around professional development and research evidence due to their knowledge of the needs of organizational divisions and key staff (Aarons et al, 2011;Austin et al, 2012;Maynard, 2010).…”
Section: Organizational Factors Promoting Access To Evidencesupporting
confidence: 72%
“…The first model refers to the evidence-based practice model (EBP), corresponding with the utilization of manualized and prescriptive clinical interventions with established fidelity procedures that have been shown to be efficacious through systematic reviews or controlled evaluation research (Barth et al, 2012). There is a large literature on understanding factors supporting implementation and practitioner use of EBPs (e.g., Aarons, Hurlburt, & Horwitz, 2011;Palinkas et al, 2011). The second model features evidence-informed practice as a multistep process through which practitioners integrate available client-based information and other agency data, external research, and their own practice experience with the goal of answering researchable practice questions (Gambrill, 2012).…”
Section: Understanding Evidence Use In Human Service Organizational Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, spoke-led outreach efforts were often focused on more grassroots efforts at a local level: in-person communications, networkbuilding activities, and advertising through popular local business. Once key partner organizations had been identified, local champions acted to both expand and to diversify the BSPAN outreach strategy in their local areas [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This superposition is usually called multiplex, multirelational, multimodal, or multivariate network (Szell et al 2010). Summarizing, a social network is a social structure made up of individuals (or organizations) called "nodes", which are tied (connected) by one or more specific types of interdependency, such as friendship, kinship, common interest, financial exchange, dislike, sexual relationships, or relationships of beliefs, knowledge or prestige (Palinkas et al 2011, Szell et al 2010. Understanding and modeling network structures have been a focus of attention in a number of diverse fields, including physics, biology, computer science, statistics, and social sciences.…”
Section: Social Networkingmentioning
confidence: 99%